Lattice specific heat for the RMIn5 (R=Gd, La,Y; M=Co, Rh) compounds: Non-magnetic contribution subtraction - Facio, J.I. (2016)
Fil: Facio, J.I. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina